Body- Place Relationship in Edna St. Vincent Millay's Poems: First Fig" and "Second Fig - Mohammad, Ghada Abdullah (Journal Of Babylon Center For Humanities Studies, 2023)
The corporeal-spatial relationship needs to be examined to understand the place of the body in the world. The body is one of the most important intellectual issues because of its semantic and ideological dimensions that formed the basis for most of the literary production. It plays a significant role in shaping individual and cultural identities. Poets and writers often use the body to explore themes of gender and race. Incorporating the body in literary works adds depth, realism, and emotional resonance. Moreover, Depicting the body in relation to power dynamics allows writers to critique societal structures and examine issues of privilege, marginalization, and resistance. Accordingly, the body began to take an analytical space in the new semiotic currents. Place plays a crucial and functional role in shaping a person's life, consolidating his being, establishing his identity, framing his nature, and then determining his priorities, orientations, and his perception of things, because the place grasps a sensory perception that begins with a person's experience in her/ his body. In poetry, place may appear as a refuge from the chaos of the world. It can be a source of inspiration, stirring the creative spirit of the poet. Furthermore, the usage of place in verse can be symbolic. It may embody notions of home, belonging, identity, or even act as a metaphor for human condition. However, the body and the place can be integrated to form the psychological powers mental, emotional and vitality of a human being. The present study deals with the body- place relationship in Edna St. Vincent Millay's poems "First Fig" and "Second Fig." It intends to show the nature of this relationship and its role as a means of struggle to get the female wits right position and function in a patriarchal community. Millay's poems present the body through the images of a "candle" in "First Fig" and a "house" in "Second Fig." The poems resonate with defiance of conventionality. In both poems, the space that includes the body is characterized by its fragility; a dark atmosphere in "First Fig" and "sand" in "Second Fig," that reflects the common vision towards the female's weak place in a masculine environment. The poet uses such fragile images as a kind of challenge to create a vigorous female existence. Millay tries to present female pride in spatial terms.